How effectively has a Just Culture been adopted? A qualitative study to analyse the attitudes and behaviours of clinicians and managers to clinical incident management within an NHS Hospital Trust and identify enablers and barriers to achieving a Just Culture. Issue 1 (27th January 2023) - Tasker, Adam; Jones, Julia; Brake, Simon
Abstract : Objectives: Just Culture aims to improve patient safety by examining the organisational and individual factors that contribute to adverse events, enabling corrective action so that errors are not repeated. This qualitative study aims to: (1) analyse whether the attitudes and behaviours of clinicians and managers are aligned with a Just Culture; (2) identify barriers and enablers to an organisation adopting a Just Culture. Methodology: This qualitative study used interviews and observation of Trust meetings to elicit the attitudes and behaviours of staff. Semistructured interviews were conducted with 13 doctors of all grades, 5 medical students and 2 managers. Five meetings that reviewed clinical incidents and mortality were observed. This was done in a single Hospital Trust in the Midlands, England. Data were thematically analysed using directed and inductive approaches. Results: There is evidence of a fair incident management process within the Trust; however, there was no agreed vision of a Just Culture and the majority of the staff were unfamiliar with the term. Negative perspectives relating to clinical incidents and their management persist among staff with many having insecurities regarding being the subject of an investigation and doubts about whether they drive improvement. Conclusion: This paper examines the significance of these findings and provides recommendations which may have application within other healthcare organisations. Major recommendations include (1) Just Culture: define an agreed vision of what Just Culture means to the Trust; (2) investigations: introduce incident management familiarisation training; (3) Learning Culture: increase face-to-face communication of outcomes of investigations and incident review; (4) investigators: establish an incident investigation team to improve the timeliness and consistency of investigations and the communication and implementation of outcomes.